Interaction between the intestinal flora and the severity of diversion colitis after low anterior resection of rectal cancer - Sun, Qiang; Shi, Yunjie; Liang, Xiaoben; Lu, Hao; Huang, Yu; Zhu, Lin; Wang, Wenqiang; Zhang, Wei; Hu, Zhiqian; Li, Xinxing (Frontiers in Oncology, 2023)
Abstract Background: Diversion colitis (DC) is nonspecific inflammation of the distal intestinal mucosa following disruption of colonic continuity with colonic dysfunction. The colonscopic score is a good tool for differentiating the severity of patients with DC. At present, no studies have analyzed the pathogenesis of DC from the perspective of the diversity and and differences of intestinal flora. Methods: Retrospective study: Clinical information were collected from patients with low rectal cancer admitted to our Hospital, from April 2017 to April 2019. These patients underwent laparoscopic low anterior resection (LAR) combined with terminal ileum enterostomy (dual-chamber). We used chi-square test to comparethe clinical baseline information, clinical symptoms, and colonscopic characteristics between different severity of DC. Prospective nested case-control study: We recruited 40 patients with laparoscopic anterior low resection combined with terminal ileum enterostomy and they were further classified into mild group and severe group according to the scores of colonscopic examinations for DC. 16s-rDNA sequencing was carried out to analyze the diversity and and differences of intestinal flora in the intestinal lavage fluid of the two groups. Results: In retrospective study, we found that age, BMI, history of diabetes, and symptoms associated with the stoma state were the independent risk factors that affect DC severity (P＜0.05). Meanwhile, age, BMI, history of diabetes and colonscopic score were found to be independent risk factors affecting the severity of diarrhea after ileostomy closure surgery(P＜0.05); In prospective nested case-control study, The results of 16s-rDNA sequencing showed that intestinal flora with high enrichment values primarily consisted of Bifidobacteriales and Prevotella in mild group, whereas that in the severe group consisted of Providencia and Dorea. The functional predictions on such two types of intestinal flora were mainly focused on lipid synthesis, glycan synthesis, metabolism, and amino acid metabolism pathways. Conclusion: After ileostomy closure surgery, a series of severe clinical symptoms might appear in DC patients. There are significant differences in local and systemic inflammatory responses, composition of intestinal flora between DC patients with different colonscopic scores, which provide a basis for the clinical interventional treatment for DC in patients with permanent stoma.